Insights into the Pyrolysis Properties of Environmentally Friendly PMVE/N2 Gas Mixtures: A Collaborative Analysis Based on Density Functional Theory and Reaction Kinetics - Haibo Dong; Haonan Chu; Yunhao Liu; Shicheng Liu; Wenyu Ye; Jiaming Yan (Applied Sciences)
With growing environmental concerns, the search for alternative gases to replace SF6 has become a key focus in the power industry. Perfluoromethyl vinyl ether (PMVE), with its low global warming potential (GWP) and excellent insulation properties, is a promising candidate. When mixed with N2, PMVE not only decreases the liquefaction temperature but also enhances insulation performance, making the gas mixture more suitable for engineering applications. In this study, reactive molecular dynamics (ReaxFF-MD) and density functional theory (DFT) calculations were combined to investigate the influence of temperature on the decomposition characteristics of a PMVE/N2 mixture. The reaction pathways and reaction enthalpy of PMVE and its major decomposition products were analyzed in detail. The results showed that, as temperature increases, the decomposition intensity of PMVE is enhanced, leading to a higher reaction rate and accelerated formation of decomposition products. Moreover, the main decomposition products of the PMVE/N2 mixture include C, C2F2, CF2, CN, CO, CF2O, F, O, and other small molecules and free radicals. The dynamic balance between the generated free radicals helps maintain the system’s insulation capacity. However, toxic decomposition byproducts such as CF2O, C2N2, and CO were also detected. This study provides valuable insights into the engineering applications of PMVE/N2 mixtures.